The use of transcranial magnetic stimulation as a treatment for movement disorders: A critical review. Issue 6 (29th April 2019) - Latorre, Anna; Rocchi, Lorenzo; Berardelli, Alfredo; Bhatia, Kailash P.; Rothwell, John C.
ABSTRACT: Background: Transcranial magnetic stimulation is a safe and painless non‐invasive brain stimulation technique that has been largely used in the past 30 years to explore cortical function in healthy participants and, inter alia, the pathophysiology of movement disorders. During the years, its use has evolved from primarily research purposes to treatment of a large variety of neurological and psychiatric diseases. In this article, we illustrate the basic principles on which the therapeutic use of transcranial magnetic stimulation is based and review the clinical trials that have been performed in patients with movement disorders. Methods: A search of the PubMed database for research and review articles was performed on therapeutic applications of transcranial magnetic stimulation in movement disorders. The search included the following conditions: Parkinson's disease, dystonia, Tourette syndrome and other chronic tic disorders, Huntington's disease and choreas, and essential tremor. The results of the studies and possible mechanistic explanations for the relatively minor effects of transcranial magnetic stimulation are discussed. Possible ways to improve the methodology and achieve greater therapeutic efficacy are discussed. Conclusion: Despite the promising and robust rationales for the use of transcranial magnetic stimulations as a treatment tool in movement disorders, the results taken as a whole are not as successful as were initially expected. There is encouraging evidence that transcranial magnetic stimulation may improve motor symptoms and depression in Parkinson's disease, but the efficacy in other movement disorders is unclear. Possible improvements in methodology are on the horizon but have yet to be implemented in large clinical studies. © 2019 International Parkinson and Movement Disorder Society © 2019 International Parkinson and Movement Disorder Society